Acute Pancreatitis: CT Severity Index, Fluid-Resuscitation Nursing Algorithms, and Lipase/CRP as Outcome Markers - Alamari, Abdulmohsen Ateeq; Adel Garsan Seed Alzahrani; Fahad Mohmmed Saead Alqhtani; Fatimah Mousa Ibrahim Alsekiny; Adel Maqbul Mutlaq Alsharar; Hussain Homoud Habibi Namazi; Mohammed Ahmed Mohammed Muyidi; Ahmed Saud Alhejaili; Hosam Hasan Alzhrani; Wazan Maeid Al-Anzi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Acute pancreatitis (AP) is a common, potentially life-threatening inflammatory condition with heterogeneous etiologies and trajectories. Early risk stratification and coordinated supportive care are pivotal to reduce necrosis, organ failure, and resource use. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To synthesize evidence on three practical pillars of inpatient AP care—radiologic grading by CT Severity Index (CTSI), fluid-resuscitation nursing algorithms, and biochemical markers (lipase and C-reactive protein, CRP)—and to propose an integrated, bedside-ready framework. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Narrative review of contemporary diagnostic and management domains summarized in this article, emphasizing: (1) imaging roles (ultrasound/CECT/MRI) and CTSI for local complications; (2) nurse-led fluid protocols (targets, choice of crystalloid, ROSE phases); and (3) serial lipase/CRP as outcome markers alongside clinical severity classifications. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> CTSI reliably stages local pancreatic/peripancreatic complications and complements clinical systems (e.g., RAC/DBC) for prognostication and timing of interventions. Nurse-delivered resuscitation algorithms with early lactated Ringer’s at 5–10 mL/kg/h, dynamic endpoints (heart rate <120 beats/min, urine output >0.5 mL/kg/h), and avoidance of overload reduce SIRS, organ failure, and length of stay. Early enteral nutrition embedded in nursing pathways improves tolerance and pain trajectories. Lipase confirms diagnosis but trends add limited prognostic value; CRP trajectories (e.g., 48–72 h) better correlate with severity and necrosis, especially when interpreted with imaging and physiology. Multidisciplinary coordination among radiology, laboratory, and nursing closes operational gaps and accelerates definitive etiologic care. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> An integrated pathway combining CTSI-guided imaging, protocolized nurse-led fluid resuscitation, and judicious use of lipase/CRP improves risk recognition, streamlines decisions, and may reduce complications and costs in AP.